The assessment of service quality for third-party logistics providers in the beverage industry. Issue 1 (1st January 2020) - Mathong, Punnatorn; Sureeyatanapas, Panitas; Arunyanart, Sirawadee; Niyamosoth, Thanawath
Abstract: The assessment of service quality has received increasing attention over the past few decades. The SERVQUAL model is an instrument that is commonly used to quantify the quality of a service. It divides "service quality" into five dimensions: tangibles, responsiveness, reliability, assurance, and empathy. SERVQUAL, however, is not intended to be instantly implemented into every industry or business sector, as items belonging to each dimension need to be adjusted to suit the characteristics of the industries assessed. This study aims to apply the SERVQUAL dimensions to the beverage transportation industry. This is done firstly by compiling assessment items from the relevant literature. The selected items are then modified to suit the beverage logistics industry and classified into the five dimensions. The validity of the items is confirmed by the item-objective congruence index and through interviews of industry experts. A pilot study is conducted to test the items' reliability using the Cronbach's alpha values. The revised version of the questionnaire can be used as an effective instrument for assessing the quality of services of the beverage transportation providers. The proposed instrument is then applied in a survey of sampled customers of a case study company. Gap analysis, quadrant analysis, point allocation, and the weighted sum methods are used to analyse the company's service quality. The importance of the five SERVQUAL dimensions is also investigated through the survey, and the results show that "reliability" is the most important aspect for retailers and wholesalers in the beverage industry.